Convergence Analysis for a Modified SP Iterative Method - Celiker, Fatma Ozturk (HINDAWI PUBLISHING CORPORATION, 2014)
We consider a new iterative method due to Kadioglu and Yildirim (2014) for further investigation. We study convergence analysis of this iterative method when applied to class of contraction mappings. Furthermore, we give a data dependence result for fixed point of contraction mappings with the help of the new iteration method.
Keywords: FIXED-POINTS; APPROXIMATION; MAPPINGS; Science & Technology - Other Topics